La acción de protección y su incidencia en los derechos humanos - Almache Vaca, Néstor Emilio (2023)
In the present degree work, an analysis of the protection action in Ecuadorian legislation is made, its antecedents, its incidence in the protection of human rights established in the Constitution and in the International Instruments ratified by the State, the denaturalization that is has evidenced during its validity, the shortcomings found for an effective and prompt response from the State before the recurrence of citizenship and the responsibility this against this constitutional guarantee, reforms will also be proposed to various Laws that contain provisions that in some way prevent a response adequate to the demand of society in the face of abuses, especially in the public sector and also in the private sector and that are related to the indicated action, as well as the necessary permanent training for Judges, Lawyers in free professional practice and public servants in general, taking into account that most of the resolutions and decisions of power emanate from the latter, which in not a few cases have violated the fundamental rights of citizens, for whom their administrative and other actions are directed.